1956
DOI: 10.2307/410583
|View full text |Cite
|
Sign up to set email alerts
|

An Outline of English Phonetics

Abstract: Illustrations was merged with this page. Written byDaniel Jones. ISBN1151840513 An Outline of English Phonetics-Daniel Jones-Google Books An Outline of English Phonetics is one of the best known books ever written for foreign students of English. In this textbook Daniel Jones drew on his unrivalled An outline of English phonetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
211
0
18

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(247 citation statements)
references
References 0 publications
5
211
0
18
Order By: Relevance
“…Syllabic structure has robust acoustic consequences on the realization of the segments of the sequence. In the seal/ceiling case, for example, the /l/ will change from the dark, coda allophone in seal to the light onset allophone in ceiling (Abercrombie, 1967;Jones, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Syllabic structure has robust acoustic consequences on the realization of the segments of the sequence. In the seal/ceiling case, for example, the /l/ will change from the dark, coda allophone in seal to the light onset allophone in ceiling (Abercrombie, 1967;Jones, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…In English , phonetic observation has revealed that the closure for the first consonant in a cluster generally is not released until after the closure for the second is formed (e . g ., Kenyon , 1951 ;Jones , 1956 ;Abercrombie , 1967 ;Catford , 1977 ;MacKay , 1978 ;Hardcastle & Roach , 1979 ;see Henderson & Repp , 1982 on acoustic consequences) . Barry (1985) , Nolan (1992) , Browman & Goldstein (1990b) , and others have shown that an initial consonant in a cluster that may sound as if it has been assimilated in place of articulation , or deleted altogether , is often in fact still articulated at its original point of articulation .…”
Section: Introductionmentioning
confidence: 99%
“…Interrogations also comprise communicative signals that accompany speech such as facial expressions and gestures as well as communicative signals transported via the prosodic features of spoken language and, specifically, its intonation. Jones (1969) defines intonation as "the variations which take place in the pitch of the voice in connected speech" (p. 275). More recent definitions go beyond pitch variation and include further parameters such as perceived duration and intensity (e.g., Ladd, 1996;Selting, 1987).…”
mentioning
confidence: 99%